Anomalous Investigation of ILS Glide Path Signals on Runway 24 at the Jakarta Air Traffic Service Center - Wildan, Muh; Wibowo, Priyo; Wicaksono, Mochamad Sugeng; Sulaiman, Muhammad Arif; Rahmadani, Eldo Tri; Prasojo, Muhamad Adimukti (Institut Teknologi Dirgantara Adisutjipto, 2025)
Precision landing guidance is critical for aircraft safety, yet recurring signal anomalies in the ILS Glide Path on runway 24 at the Jakarta Air Traffic Service Center raise concerns about approach and landing reliability. Despite compliance with standard regulations, persistent signal anomalies affecting glide slope accuracy raise concerns about safe aircraft approach. This study investigates the sources of distortion, quantifies their impact on ILS Glide Path performance, and proposes mitigation strategies. Spectrum analysis, environmental assessments, and signal evaluation through oscilloscopes and navigation analyzers were employs to identify and quantify sources of distortion. Results indicate that while composite audio signals comply with standards, navigation analyzer readings reveal persistent deviations in Difference in Depth of Modulation (DDM) due to harmonic distortions at 30 Hz and its multiples up to 450 Hz. These distortions could interfere with DDM values received by calibration aircraft, making conventional technical adjustments, such as power level settings and antenna reconfigurations, insufficient for complete resolution. Instead, alternative mitigation approaches including reducing environmental reflections, optimizing siting criteria, and refining regulatory compliance measures are recommended. These findings provide valuable insights for enhancing ILS Glide Path reliability, refining signal mitigation strategies, and ensuring regulatory compliance for safer aviation navigation systems.